Accuracy of Echocardiography to Estimate Pulmonary Artery Pressures With Exercise: A Simultaneous Invasive–Noninvasive Comparison. (April 2017) - van Riel, Annelieke C.M.J.; Opotowsky, Alexander R.; Santos, Mário; Rivero, Jose M.; Dhimitri, Andy; Mulder, Barbara J.M.; Bouma, Berto J.; Landzberg, Michael J.; Waxman, Aaron B.; Systrom, David M.; Shah, Amil M.
Abstract : Background—: Exercise echocardiography is often applied as a noninvasive strategy to screen for abnormal pulmonary hemodynamic response, but it is technically challenging, and limited data exist regarding its accuracy to estimate pulmonary arterial pressure during exercise. Methods and Results—: Among 65 patients with exertional intolerance undergoing upright invasive exercise testing, tricuspid regurgitation (TR) Doppler estimates and invasive measurement of pulmonary arterial pressure at rest and peak exercise were simultaneously obtained. TR Doppler envelopes were assessed for quality. Correlation, Bland–Altman, and receiver-operating characteristic curve analyses were performed to evaluate agreement and diagnostic accuracy. Mean age was 62±13 years, and 31% were male. High-quality (grade A) TR Doppler was present in 68% at rest and 34% at peak exercise. For grade A TR signals, echocardiographic measures of systolic pulmonary arterial pressure correlated reasonably well with invasive measurement at rest ( r =0.72, P <0.001; bias, −2.9±8.0 mm Hg) and peak exercise ( r =0.75, P <0.001; bias, −1.9±15.6 mm Hg). Lower quality TR signals (grade B and C) correlated poorly with invasive measurements overall. In patients with grade A TR signals, mean pulmonary arterial pressure-to-workload ratio at a threshold of 1.4 mm Hg/10 W was able to identify abnormal pulmonary hemodynamic response during exercise (>3.0 mm Hg/L per minute increase), with 91% sensitivity and 82% specificity (area under the curve, 0.90; 95% confidence interval, 0.77–1.0; P =0.001). Conclusions—: Agreement between echocardiographic and invasive measures of pulmonary pressures during upright exercise is good among the subset of patients with high-quality TR Doppler signal. While the limits of agreement are broad, our results suggest that in those patients, sensitivity is adequate to screen for abnormal pulmonary hemodynamic response during exercise. Abstract : Supplemental Digital Content is available in the text.